Development and evaluation of a bait station for selectively dispensing bait to invasive wild pigs - Michael J. Lavelle; Nathan P. Snow; Joe M. Halseth; John C. Kinsey; Justin A. Foster; Kurt C. VerCauteren (Wildlife Society Bulletin)
ABSTRACT Populations of invasive wild pigs (Sus scrofa; hereafter, wild pigs) are expanding, requiring cost‐effective tools for control, and disease prevention, such as toxic or vaccine baits. Specifically, development of a novel and humane toxicant is underway for control of wild pigs in the United States and Australia. A species‐specific bait station for delivering the toxic bait must be used to protect nontarget animals. Further, a bait station must be designed to maximize feeding by wild pigs by accommodating their group‐feeding behaviors. We sought to develop a bait station that delivered bait to the maximum proportion of wild pigs and excluded the most ubiquitous nontarget species, specifically white‐tailed deer (Odocoileus virginianus) and raccoons (Procyon lotor). We used direct observations and cameras during 2015 to evaluate wild pig feeding behavior and nontarget access for various sizes, arrangements, and construction materials of prototype bait stations in pen and field settings in Texas, USA. We found that a bait station constructed of 2 back‐to‐back troughs, 1.1 m in length, without a divider was sufficient for feeding the largest proportion of wild pigs in pens. Using this design of bait station at 30 field sites, we found that wild pigs fed more frequently from plastic than metal bait stations, although both bait stations reduced feeding by wild pigs compared with control sites. From near‐video imagery at 3 field sites, we identified that 80% of wild pigs (33 of 41), 0% of white‐tailed deer (0 of 7), and 17% of raccoons (1 of 6) accessed the bait stations on the final night of testing following a 2‐week acclimation and training period. Future steps toward development of a wild pig‐specific bait station include adding resistance to the lids of bait stations to completely exclude raccoons and identify baiting strategies that most efficiently acclimate wild pigs to using bait stations. Published 2018. This article is a U.S. Government work and is in the public domain in the USA.